Effect of Retort Processing on Low Sodium Instant Noodle Seasoning Based on Oil-in-Water Emulsions - Melanie Cornelia; Angeline Apriliana; Irene Triyanti (International Journal of Food Studies)
Increasing consumption of instant noodles with high sodium content could elevate the risk of cardiovascular disease. Making instant noodle seasoning in the form of an oil-in-water emulsion was expected to improve the perception of salty taste without increasing the use of salt. However, the oil concentration in the emulsion affects the perception. The addition of antioxidant and retort processing was needed to overcome the nature of the emulsion that was quite susceptible to oxidation and microbial contamination. Preliminary research determined the optimum concentration of oil and antioxidant based on physical characteristics, the perception/gustation of saltiness, and emulsion oxidative stability and the results were used for further research. The final part of the research determined the effects of retort processing on emulsion stability, the perception of saltiness, and the degree of microbial contamination. Three different oil concentrations (26, 27, and 28%) and three types of antioxidants (natural vitamin E, ascorbyl palmitate and mixed tocopherol) were applied to the instant noodle seasoning oil-in-water emulsions. The results showed that using 28% oil and mixed tocopherol had the most stability, was more viscous, and had optimum salty taste perception, which significantly extended the shelf-life of the emulsion compared with the others. Retort processing for 21.5 minutes in 123.5 °C was applied to the seasoning emulsion with 28% oil content and mixed tocopherol. Although, the microbial contamination was significantly reduced, neither the stability of emulsion nor the perception of salty taste was significantly changed by the process.